Differences in the COVID-19 Pandemic Response between South Korea and the United States: A Comparative Analysis of Culture and Policies. (March 2023) - Song, Sooho; Choi, Yunhee
The impact of the COVID-19 pandemic has varied across countries. Some countries controlled the virus relatively well, while others did not. In the United States, almost a million people died. However, South Korea's death toll is only about 12, 000 even though its population is about one-sixth of the United States. What caused the difference? We argue that public compliance to government direction is the primary reason. South Korea's collective culture valuing communal benefits helped the people conform to government directions, such as mask wearing in public places. By contrast, American people resisted the government policies that restrict individual freedom due to the individualistic culture. In South Korea, historical experiences of relatively frequent national crises led to the rise of defensive nationalism, resulting in national union. However, the United States had relatively fewer national crises, and thus nationalism did not rise. Instead, national division, xenophobia, and hatred toward Asians prevailed in the United States. Besides the cultural differences, differences in national leader's characteristics, past experiences of public health crisis, and political system also contributed to the different outcomes of the crisis.